2014
DOI: 10.1002/elan.201300597
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Biosensors for the Determination of Cardiovascular Markers: a Review

Abstract: Nowadays there is a growing interest in the development of devices for the fast and reliable detection and quantification of biomarkers associated with cardiovascular diseases (CVDs). The main objective is not only an early diagnosis of these diseases but also predicting the risk that an individual can suffer CVD. Electrochemical biosensors can play a key role in the development of low cost, portable and rapid sensing platforms for this purpose. This review discusses critically the state of the art in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 59 publications
0
48
0
Order By: Relevance
“…One hour after the onset of myocardial infarction, the myoglobin level in serum can increase to 900 ng mL -1 , or even higher. 5,32 Therefore, rapid, sensitive and reliable methods for myoglobin detection can be very useful in clinical use. In our system, the peptide-based electrochemical biosensor showed excellent analytical performance, and the high sensitivity is attributable to effective myoglobin capture of the peptide.…”
Section: Electrochemical Detection Of Myoglobinmentioning
confidence: 99%
See 1 more Smart Citation
“…One hour after the onset of myocardial infarction, the myoglobin level in serum can increase to 900 ng mL -1 , or even higher. 5,32 Therefore, rapid, sensitive and reliable methods for myoglobin detection can be very useful in clinical use. In our system, the peptide-based electrochemical biosensor showed excellent analytical performance, and the high sensitivity is attributable to effective myoglobin capture of the peptide.…”
Section: Electrochemical Detection Of Myoglobinmentioning
confidence: 99%
“…Due to its small size of 17.8 kDa, myoglobin is quickly released into circulation within 1 -3 h after symptom onset, and serves as a valuable screening molecule with high sensitivity and predictivity for AMI detection. [3][4][5] Optical biosensors, including a sandwich immunoassay with secondary labeled antibodies, enzyme-linked immunosorbent assay (ELISA), fluorescence, and surface plasma resonance (SPR), have been used for the detection of cardiac markers, such as troponin I, myoglobin, c-reactive protein (CRP), and myeloperoxidase (MPO). [6][7][8][9][10] Driven by a clinical need for pointof-care diagnostics, next-generation biosensors with improved sensitivity and specificity have attracted increasing attention in recent years, leading to the development of peptide-based sensing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of cardiac biomarkers such as cardiac troponins (cTn), myeloperoxidase (MPO), myoglobin (Mb), creatine kinase MB (CK-MB), or N-terminal pro-B type natriuretic peptide (NT-proBNP) provides an effective strategy for diagnosis and prevention where electrochemical immunosensors involving carbon nanomaterials have held a starring role for many years [58]. Some examples of recent configurations using CNTs are reviewed below and their analytical characteristics summarized in Table 2.…”
Section: Electrochemical Immunosensors Involving Carbon Nanomaterimentioning
confidence: 99%
“…Among CVDs, acute myocardial infarction (AMI) is one of the most life-threatening diseases in humans. For the detection of AMI, the concentrations of its biomarkers in blood are measured (Pedrero et al, 2014). The most commonly used biomarkers are creatine kinase-MB, myoglobin, cardiac troponin T, and cardiac troponin I (cTnI) (Stillman et al, 2011); cTnI is a subunit of the troponin complex found in cardiac muscle and is a highly specific and sensitive biomarker for the clinical diagnosis of AMI.…”
Section: Introductionmentioning
confidence: 99%